Teachers’ Challenges and Strategies in Sexual and Reproductive Health Education for Children with Intellectual Disabilities - Dyah Dwi Astuti; Duwi Pudji Astuti; Tri Widyastuti Handayani; Sumardino Sumardino (INKLUSI, 2026)
Children with intellectual disabilities require additional support in understanding sexual and reproductive health due to decision-making challenges and limited educational and socio-cultural support. This study explored teachers’ challenges and strategies in delivering such education. A qualitative descriptive design was conducted in a special school involving five teachers selected through purposive sampling. Data were collected through focus group discussions (FGDs) and analyzed using inductive content analysis. Five themes revealed challenges in managing sexual behaviors that were not aligned with cognitive development. Teachers implemented habituation, experience-based learning, and counseling to support understanding of bodily changes, social norms, and self-regulation during puberty, supported by collaboration among schools, parents, and health professionals. These findings highlight the importance of adaptive and collaborative approaches. Schools should integrate experience-based learning and strengthen partnerships with families and health professionals. Anak dengan disabilitas intelektual membutuhkan dukungan tambahan dalam memahami kesehatan seksual dan reproduksi akibat keterbatasan dalam pengambilan keputusan serta dukungan sistem pendidikan dan sosial-budaya yang masih terbatas. Penelitian ini mengeksplorasi tantangan dan strategi guru dalam memberikan edukasi tersebut. Penelitian menggunakan desain deskriptif kualitatif di Sekolah Luar Biasa dengan lima guru yang dipilih secara purposive. Data dikumpulkan melalui diskusi kelompok terarah (FGD) dan dianalisis menggunakan inductive content analysis. Hasil penelitian mengidentifikasi lima tema yang menunjukkan tantangan dalam mengelola perilaku seksual yang tidak sejalan dengan perkembangan kognitif. Guru menerapkan strategi berupa pembiasaan, pembelajaran berbasis pengalaman, dan konseling untuk mendukung pemahaman perubahan tubuh, norma sosial, serta pengaturan diri selama pubertas, melalui kolaborasi antara sekolah, orang tua, dan tenaga kesehatan. Temuan ini menegaskan pentingnya pendekatan yang adaptif dan kolaboratif. Sekolah perlu mengintegrasikan pembelajaran berbasis pengalaman serta memperkuat kemitraan dengan keluarga dan tenaga kesehatan.